ЭФФЕКТИВНОСТЬ НРАВСТВЕННОГО ВОСПИТАНИЯ ПОСРЕДСТВОМ УРОКОВ РУССКОГО ЯЗЫКА И ЛИТЕРАТУРЫ - Сайболова, А.А. (My University, 2019)
Аннотация В данной статье рассматривается важность нравственного воспитания подрастающего поколения на уроках русского языка и литературы. В процессе обучения и воспитания глав- ная задача педагога – научить ребят видеть и чувствовать мир, открывать доброе сердце с по- мощью мастеров слова, а именно прививать студентам такие чувства, как уважение к стар- шим, сострадание к слабому, бескорыстие, вежливость, милосердие,отзывчивость. Эффек- тивность нравственного воспитания заключается в нравственно-эмоциональном заряде ме- тодов и приемов педагога. Abstract This article discusses the importance of the moral education of the younger generation in the lessons of the Russian language and literature. In the process of training and education, the main task of the teacher is to teach children to see and feel the world, to open a good heart with the help of masters of the word, namely to inculcate in students such feelings as respect for elders, compas- sion for the weak, selflessness, politeness, compassion. The effectiveness of moral education lies in the moral and emotional charge of the methods and techniques of the teacher.
Efficiency of moral education by means of russian language lessons and literature
Keywords: национальные и общественные ценности; нравственные заповеди; литература-источник ценностей; милосердие; national and social values; moral precepts; literature; source of values; mercy